2005
DOI: 10.1161/01.hyp.0000154785.50570.63
|View full text |Cite
|
Sign up to set email alerts
|

Agonistic Autoantibodies to the AT1 Receptor in a Transgenic Rat Model of Preeclampsia

Abstract: Abstract-We used rats transgenic for the human angiotensinogen (hAogen) gene and the human renin (hRen) gene and crossed the strains to produce a model of preeclampsia in the dams. The female (nϭ9) hAogen ϫ male hRen cross had severe (telemetry-measured) hypertension and albuminuria, which developed during the last trimester of pregnancy and subsided after delivery. The converse cross (nϭ9) and control (nϭ9) SD rats did not. We demonstrated that the female hAogen ϫ male hRen cross had agonistic antibodies capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
107
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(113 citation statements)
references
References 26 publications
4
107
1
1
Order By: Relevance
“…15 Thus, the antibody in combination with Ն1 other factors could still be a relevant pathogenetic factor for pregnancy pathology, as also indicated by recent findings of Dechend et al in transgenic rats. 8 Our study has 2 major implications. The clinical importance of the AT 1 -AA has changed in the light of evidence characterizing it as an early but not entirely specific marker for preeclampsia.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…15 Thus, the antibody in combination with Ն1 other factors could still be a relevant pathogenetic factor for pregnancy pathology, as also indicated by recent findings of Dechend et al in transgenic rats. 8 Our study has 2 major implications. The clinical importance of the AT 1 -AA has changed in the light of evidence characterizing it as an early but not entirely specific marker for preeclampsia.…”
Section: Discussionmentioning
confidence: 86%
“…The fact that the AT 1 -AA is an interesting candidate for mediating or even causing the disease was further supported by the finding that a transgenic rat model of preeclampsia is also characterized by the presence of the AT 1 -AA. 8 However, decisive evidence that the detected autoantibody is causative for preeclampsia has not yet been provided. Attention was focused on determining whether AT 1 -AA precedes the clinical symptoms of preeclampsia or is only a secondary effect of clinically evident preeclampsia and therefore not the primary cause of the disease.…”
mentioning
confidence: 99%
“…Dechend and colleagues 64 used the cardiomyocyte contraction assay to detect the presence of AT1 agonistic antibody in pregnant transgenic rats overexpressing components of the human renin angiotensin system. Peptide competition experiments showed that the antibody interacted with the same 7-aa epitope on the second extracellular loop of the AT1 receptor defined by AT1-AA obtained from women with preeclampsia.…”
Section: Renin-angiotensin Systemmentioning
confidence: 99%
“…19 The dams expressing human angiotensinogen develop hypertension and proteinuria during pregnancy after mating with males expressing the human renin. 18 The offspring are growth restricted, 20 comparable to what is observed in spontaneously occurring, early-onset preeclampsia in pregnant women. The model exhibits pathological endovascular trophoblast cell invasion with altered uteroplacental vascular remodeling.…”
mentioning
confidence: 73%
“…Because shallow endovascular trophoblast cell invasion is considered to be causal for the pathological event initiating preeclampsia symptoms and signs, 17 we hypothesized that depletion or reduction of NK cells associated with increased trophoblast cell invasion ameliorates the preeclamptic phenotype in our rat model. We worked with our double-transgenic rat preeclamptic model where the preeclamptic phenotype has been established in rats 18 and mice. 19 The dams expressing human angiotensinogen develop hypertension and proteinuria during pregnancy after mating with males expressing the human renin.…”
mentioning
confidence: 99%